Everyday Politics of Dadan Contracts in the Chittagong Hill Tracts, Bangladesh - Bablu Chakma (Development and Change, 2022)
This article analyses processes of dadan contract negotiations between Bengali intermediaries and indigenous Tanchangya peasants of the Chittagong Hill Tracts, Bangladesh, in the culantro sector. The research extends the debates on the dadan system and interlocked market relationships by highlighting everyday dynamics of dadan and the issue of `just price' that arises from such contracts. The article argues that the dadan loan system leads to greater spaces for exploitation. While it facilitates peasants' access to credit for agricultural and social reproduction and the supply of culantro to wider national markets, it also creates a dependency of Tanchangya peasants on Bengali moneylending traders. Such an analysis reveals the limitations of existing studies on dadan in accounting for the social, cultural and political aspects of dadan contracts, alongside their economic aspects. The article concludes that contested moralities associated with the pursuit of familial subsistence and contractual obligations shape peasants' decisions and strategies concerning such contracts.
Keywords: 300